Resource Diversification in Turkey’s Electricity generation - Dilek, Serkan; Konak, Ali (Holistence Publications, 2022)
Natural gas, fuel oil, coal, lignite, geothermal, wind, solar, hydraulics, etc. are used in electricity generation, which is one of the most important inputs of industrial production. Being dependent on one or several sources of electricity generation is an important risk factor for the industry and economy of the country. A problem in the supply of one of these resources or an increase in prices may adversely affect the entire country’s industry and therefore the economy. In this research, we measured the concentration of the resources Turkey uses in electricity generation between the years 2000-2020. We used the Herfindahl-Hirschman and concentration indices. The resource concentration in Turkey’s electricity production started to decrease towards the end of the period. Reducing the use of natural gas and more use of geothermal, solar, and wind resources have been effective in this result. While Turkey produced 49.8% of its electricity production using natural gas in 2008, this rate decreased to 23.1% in 2020. While Turkey provided 95.6% of its electricity production from four sources in 2002, this rate decreased to 81.3% in 2020. These rates show that Turkey has increased diversification in electricity generation, but this diversification is still not sufficient.
Keywords: 13. Climate action; 7. Clean energy